Polyethyleneimine and Poly(ethylene glycol) Functionalized Oligoester Based Polycationic Particles. (29th April 2018) - Mazurek-Budzynska, Magdalena; Balk, Maria; Behl, Marc; Lendlein, Andreas
ABSTRACT: Polycationic particles based on a degradable oligoester core are interesting candidate materials for the transfection of polyanionic macromolecules like DNA, which would enable the degradation after delivery of condensed molecules. Good transfection efficiencies can be obtained when the size of the polyplex (containing both polycationic nanoparticles and polyanionic macromolecules) does not exceed 120 nm. Therefore, here we explored how size, but also dispersity, and surface charge of these carrier systems can be adjusted by variation of the block copolymer composition or the presence and ratio of a co-assembly agent. Polycationic particles were obtained based on an amphiphilic triblock copolymer from oligo[(ε-caprolactone)-co-glycolide] (CG) functionalized with polyethyleneimine (PEI) and diblock copolymer based on poly(ethylene glycol) (PEG) modified with CG. A second series of particles was created, in which the oligoester blocks contained only ε-caprolactone units, therefore the effect of the presence of glycolide units was also studied. In both series, the ratio between di- and triblock copolymers was systematically varied. Nano-sized particles ranging from 34.5 ± 0.2 nm to 97.9 ± 0.3 nm with controllable positive surface charges between 2.9 ± 0.2 mV and 18.1 ± 0.5 mV were obtained by self-assembly in PBS solution under intensive stirring. The incorporation of PEG-C diblock copolymers resulted in an increase of particle size, however no specific relation between composition, size, and polydispersity was observed. In case of PEG-CG diblock copolymers a rather systematic increase of the particles' size with increasing content of diblock copolymer was shown. Furthermore, with a decrease of content of diblock copolymer in the particle structure zeta potential strongly increased. Additionally, the content of glycolide units in triblock copolymer increased the zeta potential of PEI-CG-PEI-based particles in comparison to PEI-C-PEI-based ones. Therefore, obtained particles could be used as potential target-oriented polycationic macromolecules for carrier systems.